A Case Series Demonstrating the Feasibility of Microdosing as a Bridging Method to Enable a Comfortable and Effective Transition From Prescribed Methadone to Buprenorphine ORT (Opiate Replacement Therapy), Without Initial Methadone Dose Reduction or Cessation, in UK Community Addiction Settings - Zelda Summers; Jennie Rankine; Stuart Fisher (BJPsych Open)
Aims: For patients prescribed methadone wishing to access buprenorphine ORT, the current practice is to reduce the methadone dose to 30/40 ml and cessation of methadone for 48 hrs prior to the switch. This exposes these patients to risk of psychological, physical distress or relapse into non-prescribed opiate use.